Applications of Gravity Method Based on Satellite Image Anomaly Data to Identify Subsurface Structures - Althafunnisa, Namyra Aisha; Herbianto, Sheren Aurellya; Setyawan, Agus (Journal of Physics and Its Applications, 2024)
We have reviewed several research related to the estimation of subsurface structure on several area in Indonesia using gravity method based on satellite image. There are located in Semarang City, Mount Tandikat, Mount Muria, Majene Earthquake Affected Area, and Mount Merapi-Merbabu. The aim of this literature study is to determine the accuracy of satellite gravity data to identify and model subsurface structures by testing them in several cases. Data processing was carried out starting from the free air anomaly and then field correction was carried out to obtain the Bouguer anomaly. Moreover, different advanced processing is carried out, such as gradient analysis, 2D and 3D modeling. The software used includes GRAV2DC, Gravblox, Bloxer, and Grav3D.The results show variations in rock density and subsurface structure at each location. Subsurface modeling includes rock types, faults and basins that can help understand local geology. The study also shows estimates of the thickness of the sediment layers at several research locations. The research results show variations in rock density in various locations (granite, sandstone, andesite, mudstone) with different density values (between 1 g/cm³ to 2.9 g/cm³). Generally, gravity data from satellite images can provide subsurface information such as lithology, geological potential, the presence of hydrothermal pathways and structures. Regarding the type of fault, it is necessary to carry out geological observations in the field and cannot just rely on the results of gravity modeling. Furthermore, the results of gravity mapping will play an important role in disaster risk management and understanding geodynamics in the area studied.